Pharmacokinetics, safety, and patient acceptability of subcutaneous versus intramuscular testosterone injection for gender-affirming therapy: A pilot study. (15th March 2018) - Wilson, David M.; Kiang, Tony K. L.; Ensom, Mary H. H.
Abstract : Purpose: Results of a study comparing testosterone exposure and tolerability with subcutaneous versus i.m. administration are presented. Methods: In a prospective, open-label, crossover study, adult participants already on stable i.m. testosterone gender-affirming therapy self-injected testosterone cypionate or enanthate i.m. for 3 weeks followed by subcutaneous injections for 8 weeks. Trough serum testosterone concentrations were determined weekly, and serial total serum testosterone (TST) concentrations were determined on postinjection days 1, 3, and 5 of weeks 3 and 11. Hemoglobin and alanine transaminase (ALT) levels were measured at week 3 (the first visit), with repeat measurements at week 11 (the final visit). The dose-normalized area under the time–concentration curve (AUC) was calculated during weeks 3 and 11. Results: Fourteen transgender males (mean age, 30 ± 10 years) participated in the study. The mean hemoglobin values at the first and final visits were 160 ± 9 and 153 ± 9 g/L, respectively ( p > 0.05); the mean ALT values were 18 ± 6 and 21 ± 10 IU/L ( p > 0.05). Total testosterone exposure was comparable with subcutaneous versus i.m. injection (mean AUC, 1.7 ± 0.6 nmol·days/L/mg versus 1.9 ± 0.6 nmol·days/L/mg; p > 0.05). Information collected via weekly questionnaires indicated that the subcutaneous route was more tolerable, with lower self-reported scores for preinjection anxiety, pain during injection, and postinjection pain. Conclusion: The subcutaneous route for the injection of testosterone was well tolerated and appeared to be as effective as i.m. injection in delivering equivalent TST levels, although there was wide intrapatient and interpatient variability.